2017
DOI: 10.1017/s0950268816003149
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of immunodeficiency-related death in a cohort of low-income people living with HIV: a competing risks survival analysis

Abstract: We conducted a survival analysis with competing risks to estimate the mortality rate and predictive factors for immunodeficiency-related death in people living with HIV/AIDS (PLWH) in northeast Brazil. A cohort with 2372 PLWH was enrolled between July 2007 and June 2010 and monitored until 31 December 2012 at two healthcare centres. The event of interest was immunodeficiency-related death, which was defined based on the Coding Causes of Death in HIV Protocol (CoDe). The predictor variables were: sociodemograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…These results were not in agreement with those reported from several developed countries [28]. In a study on low-income individuals in Brazil, Albuquerque et al claimed that tuberculosis, anemia, and CD4 count lower than 200 cell/mm 2 were the main reasons for NARM [22].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…These results were not in agreement with those reported from several developed countries [28]. In a study on low-income individuals in Brazil, Albuquerque et al claimed that tuberculosis, anemia, and CD4 count lower than 200 cell/mm 2 were the main reasons for NARM [22].…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, several cohort studies have demonstrated that HIV/AIDS-related conditions are the most frequent causes of death [2, 3]. However, the causes of mortality, including non-AIDS-related malignancies, cancers, liver and renal failures, cardiovascular diseases, and drug abuse are getting more diverse [10, 22, 23]. Despite the large number of studies conducted on the causes of death among PLWH, no efficient study has been performed in this field in Iran up to now.…”
Section: Introductionmentioning
confidence: 99%
“…Higher mortality rates among PLWH in Brazil [ 141 , 142 , 143 , 144 , 145 , 146 , 147 ] and Mexico [ 44 ] have been associated with SU. Brazilian PLWH using drugs had a relative mortality risk of 3.1 compared to non-SU [ 143 ].…”
Section: Resultsmentioning
confidence: 99%
“…Este problema é relatado em outros países e sistemas de saúde 83,84 , assim como por outros investigadores no Brasil e cidades do Estado de São Paulo [85][86][87][88] Com a abordagem das causas específicas de mortalidade, conseguimos investigar com detalhe o impacto dos determinantes da sobrevida e seu efeito em cada mortalidade específica. Alguns estudos utilizaram a metodologia de riscos competitivos em pacientes com coinfecção TB-HIV, inclusive um nacional com dados de dois centros 93 . Porém, para uma coorte geral de pacientes com TB, somente conhecemos um estudo que empregou esta metodologia para estimar a sobrevida a longo-prazo 94 .…”
Section: Análise Crítica Do Artigounclassified